Homogeneity and trends in long-term rainfall data, Kelantan River Basin, Malaysia - Che Ros F.; Tosaka H.; Sidek L.M.; Basri H. (Taylor and Francis Ltd., 2023)
El Nino-Southern Oscillation; hydrological modeling; La Nina; monsoon; numerical model; rainfall-runoff modeling; time series analysis; Kelantan; Kelantan Basin; Malaysia; West Malaysia